Lateralization and localization of epilepsy related hemodynamic foci using presurgical fMRI. Issue 1 (January 2015) - Zhang, Clara Huishi; Lu, Yunfeng; Brinkmann, Benjamin; Welker, Kirk; Worrell, Gregory; He, Bin
Highlights Spatial ICA on resting state fMRI revealed hemodynamic foci that are concordant with surgical resection. A novel IC selection algorithm basing on the concept of lateralization was proposed. Method was verified in healthy subjects with motor tasks and during resting state.